O edifício como articulador morfofuncional do entorno urbano : o bairro Enseada do Suá (Vitória-ES) - Lamego, Marcos Queiroz (2013)
It is verified, currently in the Brazilian cities, that the dominance of an architecture with features causing segregations constituting a fragmented urban tissue, with nonfunctional urban spaces and / or buildings that form physical barriers to visibilit